2000
DOI: 10.1080/00050060008260330
|View full text |Cite
|
Sign up to set email alerts
|

Australian psychology and Australia's indigenous people: Existing and emerging narratives

Abstract: his brief overview of psychological research with Indigenous people of Australia attempts to apprehend T the broad, underlying narratives of previous research in terms of its sociopolitical aims. It then considers the debate about whether the moral precept of social responsibility is compatible with scientific values that underpin psychological research, and argues that a socially responsible psychology is one that engages in self-reflection on its biases and prejudices, methodologies, and systems of ethics. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Yet as many of the alternate approaches outlined above suggest, psychology as a cultural practice needs to pay particular attention to the truth claims that it makes, and the practices that it engages in. What this requires is a willingness to engage with the critiques that are made of psychology, with the aim being a critical analysis of the epistemological foundations of the discipline, rather than assuming a defensive posture (Davidson et al, 2000). In this way we may be better equipped to challenge the epistemic violence that is often enacted in the name of the discipline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet as many of the alternate approaches outlined above suggest, psychology as a cultural practice needs to pay particular attention to the truth claims that it makes, and the practices that it engages in. What this requires is a willingness to engage with the critiques that are made of psychology, with the aim being a critical analysis of the epistemological foundations of the discipline, rather than assuming a defensive posture (Davidson et al, 2000). In this way we may be better equipped to challenge the epistemic violence that is often enacted in the name of the discipline.…”
Section: Discussionmentioning
confidence: 99%
“…Intimately related to this transparency is a form of critical reflexivity, which seeks to acknowledge the histories of oppression that structure subjectivities within contemporary Australia, and which may often be played out within the field of practice. What this reflexivity requires, then, is an increased role for the sociopolitical within psychology, and a continued willingness from practitioners, academics and the discipline more generally to speak out about oppressive practices, with which psychology is often complicit (Davidson, Sanson, & Gridley, 2000).…”
mentioning
confidence: 99%
“…The congress's complete lack of attention to such questions, alongside the absence of any Indigenous content in the conference's scientific or even social program, acted as a trigger point for the community psychologists in attendance to reflect on their social responsibility. As Davidson et al (2000) observed in reviewing a century of psychological research with Australia's Indigenous people, the challenge was then, and continues to be today:…”
Section: Engagement With Indigenous Issuesmentioning
confidence: 99%
“…There is a large body of psychological research focusing on Aboriginal people, but much of the earlier research was framed by, and reinforced, the prevailing belief systems. For example, according to Davidson, Sanson and Gridley (2000), employment difficulties were explained by psychologists in terms of genetics and cultural inferiority, and motivational theories were used to explain educational underperformance. Even when research became more culturally sensitive (e.g., assessing performance on familiar tasks rather than Western tests), the findings were couched in terms of genetics and culture, with the solution to the “problem” being a radical cultural reconditioning (Davidson et al, 2000).…”
Section: The Contextmentioning
confidence: 99%